Investment Feasibility Analysis in Developing Medicinal Plant Business as an Economic Diversification Effort in Asahan Regency - Rahmawani, Rahmawani; Syah, Syafrial; Tanjung, Adetia Azmi; Anggeraini, Faulia (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the feasibility of investment in the development of medicinal plant businesses in Asahan Regency as an effort to diversify the economy. The method used is quantitative research with a descriptive approach, including SWOT analysis to identify strengths, weaknesses, opportunities, and threats, and PESTEL analysis to evaluate external factors that affect the business. In addition, a capital budgeting analysis was carried out using NPV (Net Present Value), PI (Profitability Index), and PP (Payback Period) to determine the feasibility of investment. The results of the SWOT analysis show that Asahan Regency has high natural resource potential and government support, although there are challenges such as limited human resource quality and infrastructure. PESTEL analysis reveals that political stability and positive economic growth support the development of the medicinal plant sector, while environmental risks and policy changes need to be watched out for. The NPV calculation produces a value of around IDR 11,636,364, indicating that this project is profitable at a 10% discount rate. The Profitability Index of 2.5 indicates investment feasibility, and the Payback Period of around 0.67 years (8 months) indicates a short time to reach breakeven. The conclusion of this study is that Asahan Regency is a suitable location for cultivating medicinal plants. Increasing human resource capacity and infrastructure development are essential to maximize investment potential in this sector. This study provides recommendations for stakeholders to improve training for farmers.